Snapchat and child sexual abuse in sport: Protecting child athletes in the social media age. Issue 1 (February 2020) - Sanderson, Jimmy; Weathers, Melinda R.
Highlights: Social media technologies are contributing to sexual abuse of young athletes. Snapchat, with its allure of privacy is used by coaches to engage in sexual abuse. Snapchat facilitates abuse moving from virtual to physical contexts. Policies and Programming are needed to educate coaches, parents, and athletes. These initiatives can help protect the integrity of sport in the digital age. Abstract: Child sexual abuse is a pervasive problem that sport organizations must confront to protect the integrity of sport. While previous researchers have examined this topic, few have explored the role that technology plays. The authors address this gap by examining how coach perpetrators utilize Snapchat to facilitate sexual abuse, using Cense and Brackenridge's (2001) Temporal Model of Sexual Abuse with Children and Young Persons in Sport as a framework. Analysis of 99 media reports from 2013 to 2018 found that Snapchat provides motivation for coach perpetrators to sexually abuse that allowed them, in varied ways, to overcome internal inhibitions, external barriers, and break down victim resistance. The results indicate that youth sport organizations must develop clear policies that govern coach-athlete communication and relationships in the digital age. To further protect young athletes, youth sport organizations must develop programming to educate parents and athletes on these boundaries, to increase understanding about how sexual abuse and sexual maltreatment occur in virtual spaces.